2020
DOI: 10.1002/vzj2.20006
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing soil piping networks in loess‐derived soils using ground‐penetrating radar

Abstract: Soil piping remains a relatively unexplored phenomenon despite its substantial impacts on water and sediment transfer at the watershed scale at numerous locations around the world. One of the main limitations regarding the study of this singular process is the characterization of the pipe networks (in terms of number, position, dimensions, and connectivity of pipes). In this context, noninvasive subsurface imaging using ground-penetrating radar (GPR) has proven to be a promising technique. This study used two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…This study in a complex way has confirmed that GPR can be used to detect soil pipes: this is in accordance with previous reports [7,[18][19][20][21]. The reflections on radargrams that indicate soil pipes are well visible because there are significant differences in radar-wave response given by pipes filled with air and with water at the bottom (Figures 4e, 7d and 10c), and with the surrounding soil.…”
Section: Suitability Of Gpr Application For Soil Pipe Detectionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study in a complex way has confirmed that GPR can be used to detect soil pipes: this is in accordance with previous reports [7,[18][19][20][21]. The reflections on radargrams that indicate soil pipes are well visible because there are significant differences in radar-wave response given by pipes filled with air and with water at the bottom (Figures 4e, 7d and 10c), and with the surrounding soil.…”
Section: Suitability Of Gpr Application For Soil Pipe Detectionsupporting
confidence: 91%
“…Among these methods, GPR has received the most attention, even though it seems that the potential of this method has not yet been fully exploited. Most reports have presented the preliminary results of GPR application in the detection of soil pipes [7,8,20], including only short conference abstracts [18,19]. On one occasion GPR was used to establish hydrological connectivity between pipes through the use of a tracer solution [21] and to estimate the pipe length [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is common knowledge that detecting accuracy is vital to the investigation of a buried water infrastructure. A variety of data processing techniques have been proposed to improve the accuracy of GPR imaging [2][3][4][5][6]. Edge detection is a technique formerly used by computer engineers in the analysis of images to outline the essential information of the data [7][8][9].…”
Section: Introductionmentioning
confidence: 99%